Crooks, crime and corruption (London : Chancellor Press, 2002)
In Crooks, Crime and Corruption, is a fascinating line-up of notorious crooks and criminals, villains, thieves and swindlers, from the Moors, murders and Charles Manson to Al Capone and the man who sold the Eiffel Tower -twice.
rua 27/03/15
Loans
Keywords: Crime; Criminals